Evolution of bopA Gene in Burkholderia: A Case of Convergent Evolution as a Mechanism for Bacterial Autophagy Evasion. (27th November 2016) - Yu, Dong; Yin, Zhiqiu; Jin, Yuan; Zhou, Jing; Ren, Hongguang; Hu, Mingda; Li, Beiping; Zhou, Wei; Liang, Long; Yue, Junjie
Abstract : Autophagy is an important defense mechanism targeting intracellular bacteria to restrict their survival and growth. On the other hand, several intracellular pathogens have developed an antiautophagy mechanism to facilitate their own replication or intracellular survival. Up to now, no information about the origin or evolution of the antiautophagic genes in bacteria is available. BopA is an effector protein secreted by Burkholderia pseudomallei via the type three secretion system, and it has been shown to play a pivotal role in their escape from autophagy. The evolutionary origin of bopA was examined in this work. Sequence similarity searches for BopA showed that no homolog of BopA was detected in eukaryotes. However, eukaryotic linear motifs were detected in BopA. The phylogenetic tree of the BopA proteins in our analysis is congruent with the species phylogeny derived from housekeeping genes. Moreover, there was no obvious difference in GC content values of bopA gene and their respective genomes. Integrated information on the taxonomic distribution, phylogenetic relationships, and GC content of the bopA gene of Burkholderia revealed that this gene was acquired via convergent evolution, not from eukaryotic host through horizontal gene transfer (HGT) event. This work has, for the first time, characterized the evolutionary mechanism of bacterial evasion of autophagy. The results of this study clearly demonstrated the role of convergent evolution in the evolution of how bacteria evade autophagy.